Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1620/tjem.215.227
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Specific Silencing of the Human Gene Encoding Succinyl-CoA: 3-Ketoacid CoA Transferase

Abstract: The human succinyl-CoA: 3-ketoacid CoA transferase (SCOT) gene encodes the ketolytic enzyme that functions in the mitochondrial matrix. The activation of acetoacetate to acetoacetyl-CoA by SCOT is essential for the use of ketone bodies as an energy source. The ketolytic capacity of tissues is proportional to their level of SCOT activity. Normal hepatocytes, the site of ketone body synthesis, have no detectable SCOT protein. The absence of SCOT in hepatocytes is an important element in energy metabolism, suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…The ability of AA to stimulate cell proliferation in a SCOT-independent manner was further corroborated by showing that AA also dose-dependently promoted proliferation of HepG2 hepatocellular cells, which is known not to express SCOT protein (Fig. 4b) (65). Previous studies found that SCOT activity was inhibited by AA at concentrations greater than 5 mM (66,67).…”
Section: Aa Accelerates Muscle Regeneration By Stimulating Satellite supporting
confidence: 70%
“…The ability of AA to stimulate cell proliferation in a SCOT-independent manner was further corroborated by showing that AA also dose-dependently promoted proliferation of HepG2 hepatocellular cells, which is known not to express SCOT protein (Fig. 4b) (65). Previous studies found that SCOT activity was inhibited by AA at concentrations greater than 5 mM (66,67).…”
Section: Aa Accelerates Muscle Regeneration By Stimulating Satellite supporting
confidence: 70%
“…Ketone bodies cannot be metabolized in liver because the tissue lacks 3-oxoacid CoA transferase (20), and they are therefore exported out of the liver to other tissues where they are used as a source of energy. ␤HB and AcAc increase between 1 and 2 mM in blood and liver of rats when fasting as the liver switches to fatty acid oxidation (21), increasing to as much as 6 -8 mM in liver during prolonged starvation (22).…”
Section: Resultsmentioning
confidence: 99%
“…A previous report showed that the promoter region of OXCT1 harbors two GC-box sequences which are potential binding sites of transcription factor SP1 [15]; however, the precise contribution of these GC-box sequences to OXCT1 transcription has not been fully explored. Our western blot and qRT-PCR analysis revealed that knockdown of SP1 by shRNAs or blocking SP1 transactivity by mithramycin A (MIT), a specific SP1 inhibitor, significantly decreased OXCT1 expression level in serum-starved HepG2 cells ( Figure 3F and Supplementary information, Figure S3C).…”
Section: Activation Of Mtorc2-akt-sp1 Signaling Induces Oxct1 Expressmentioning
confidence: 99%
“…For the whole organism, ketone bodies provide a fast and efficient way for energy supply during starvation, which links dietary lipids or adipose triglycerides to the TCA cycle and respiratory chain. As a key enzyme of ketolysis, OXCT1 is expressed abundantly in heart, brain and kidney; however, its expression is found to be repressed in adult liver and liver cell lines [14,15], largely considered as a mechanism to prevent a futile cycle of ketone body synthesis and catabolism in the same tissue. Hence, while it is well established that the liver is the major factory for ketone body production, up to date, there is no documentation showing that adult human liver cells could utilize ketone bodies as energy sources, at least to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%